Strategi Pembelajaran Dialogis dalam Pendidikan Agama Islam untuk Menguatkan Sikap Toleransi Siswa di Era Digital - Muhammad Ali Subkan; Achmad Syaifur Rijal; Mudzakkir Ali (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study examines dialogic learning strategies in Islamic Religious Education as an effort to strengthen students’ tolerance in the digital era. The background of this study is based on the increasing need for religious education that not only develops students’ cognitive understanding of Islamic teachings but also shapes inclusive, empathetic, and tolerant social attitudes. The rapid growth of digital media has exposed students to various religious narratives, including unverified information, hate speech, and intolerant discourse. Therefore, Islamic Religious Education needs a learning strategy that encourages critical thinking, respectful dialogue, and contextual understanding of religious values. This study employs a qualitative approach using library research. Data were collected from books, journal articles, policy documents, and relevant academic sources related to dialogic learning, Islamic Religious Education, religious moderation, tolerance, and digital literacy. The data were analyzed using descriptive qualitative content analysis. The findings show that dialogic learning can strengthen students’ tolerance through open questioning, reflective discussion, active listening, value clarification, contextual case analysis, and collaborative reflection. In the context of Islamic Religious Education, this strategy helps students internalize Islamic values such as tasamuh, justice, balance, ukhuwah, and rahmatan lil ‘alamin. The study also reveals that dialogic learning is relevant for addressing digital-era challenges, particularly by guiding students to critically evaluate religious content, avoid hate speech, and practice ethical communication in online spaces. This study concludes that dialogic learning is a relevant pedagogical strategy for developing tolerant, critical, and socially responsible students in Islamic Religious Education.